Politeness Strategies in Arabic-Indonesian Classroom Communication: A Sociolinguistic Study - Moh Iqbal Dwi Hidayatullah; Mahbub Humaidi Aziz; Muhammad Auladun Akbar; Aulia Rahman; Fathorrahman Fathorrahman (Al-Jawhar : Journal of Arabic Language, 2026)
Linguistic politeness is an essential aspect of fostering effective communication and creating a conducive learning environment in foreign language education. This study aims to analyze the politeness strategies employed in Arabic language learning interactions at MAN 2 Kota Batu from a sociolinguistic perspective. The study adopted a descriptive qualitative approach, with data sources consisting of teachers’ and students’ utterances during Arabic language instruction, interview data, and classroom observations. Data were analyzed using Brown and Levinson’s politeness theory, Holmes’ language choice theory, Hymes’ ethnography of communication, and Poplack’s code-switching theory. The findings reveal that teachers employed various politeness strategies, including softened direct strategies, positive politeness, negative politeness, indirect strategies, and avoidance strategies. These strategies were used in delivering instructions, making requests, giving reprimands, and providing corrective feedback to students. Furthermore, Arabic–Indonesian code-switching and code-mixing were found to serve important pedagogical and social functions, including clarifying instructional content, facilitating students’ comprehension, maintaining interpersonal relationships between teachers and students, and constructing a bilingual classroom identity. In the process of correcting language errors, teachers employed recasts, prompting, indirect correction, and praise-before-correction techniques to preserve students’ confidence. Students’ responses indicated that the implementation of these politeness strategies enhanced learning comfort, classroom participation, willingness to answer questions, and learning motivation. The study concludes that linguistic politeness functions not only as a communicative tool but also as a socio-pedagogical strategy that supports the effectiveness of bilingual Arabic learning in the madrasah context.